+0  
 
0
276
2
avatar

Compute \(1 \cdot \frac {1}{2} + 2 \cdot \frac {1}{4} + 3 \cdot \frac {1}{8} + \dots + n \cdot \frac {1}{2^n} + \dotsb.\)

Guest Jul 20, 2017
edited by Guest  Jul 20, 2017

Best Answer 

 #2
avatar+19653 
+1

Compute

\(1 \cdot \frac {1}{2} + 2 \cdot \frac {1}{4} + 3 \cdot \frac {1}{8} + \dots + n \cdot \frac {1}{2^n} + \dotsb.\)

 

Let \(r =\frac12\)

 

\(\begin{array}{|rcll|} \hline s_n &=& 1 \cdot \frac {1}{2} + 2 \cdot \frac {1}{4} + 3 \cdot \frac {1}{8} + \dots + n \cdot \frac {1}{2^n} \\\\ && r = \frac12 \\\\ \hline s_n &=& 1\cdot r + 2\cdot r^2 + 3\cdot r^3 + \dots + n \cdot r^n \\ rs_n &=& \qquad \quad 1\cdot r^2 + 2\cdot r^3 + \dots + (n-1) \cdot r^n + n\cdot r^{n+1} \\ \hline s_n -r\cdot s_n &=& r+r^2+r^3+ \dots +r^n-n\cdot r^{n+1} \\ s_n\cdot(1-r) &=& \underbrace{( r+r^2+r^3+ \dots +r^n )}_{=S_n} -n\cdot r^{n+1} \\ \hline && S_n = r+r^2+r^3+ \dots +r^n \\ && rS_n = \quad r^2+r^3 + \dots + r^{n+1} \\ \hline && S_n -r\cdot S_n = r - r^{n+1} \\ && S_n\cdot (1-r) = r - r^{n+1} \\ && S_n = \frac{r - r^{n+1}}{1-r} \\ \hline s_n\cdot(1-r) &=& \underbrace{( r+r^2+r^3+ \dots +r^n )}_{=S_n} -n\cdot r^{n+1} \\ s_n\cdot(1-r) &=& \frac{r - r^{n+1}}{1-r} -n\cdot r^{n+1} \\ s_n &=& \frac{1}{1-r} \cdot \Big( \frac{r - r^{n+1}}{1-r} -n\cdot r^{n+1} \Big) \\\\ && \frac{1}{1-r} = 2 \\\\ s_n &=& 2 \cdot \Big( 2\cdot(r - r^{n+1}) -n\cdot r^{n+1} \Big) \\ s_n &=& 2 \cdot ( 2\cdot r - 2\cdot r^{n+1} - n\cdot r^{n+1} ) \\ s_n &=& 2 \cdot r\cdot ( 2 - 2\cdot r^n - n\cdot r^n ) \\ \\ \mathbf{s_n} & \mathbf{=} & \mathbf{2 \cdot r\cdot \Big( 2 - (2+n)\cdot r^n \Big)} \quad & | \quad r=\frac12 \\ \\ s_n & = & 2 \cdot \frac12 \cdot \Big( 2 - (2+n)\cdot (\frac12)^n \Big) \\ s_n & = & 2 - (2+n)\cdot \frac{1}{2^n} \\ \\ \mathbf{s_n} & \mathbf{=} & \mathbf{2 - \frac{2+n}{2^n} } \\ \hline \end{array}\)

 

laugh

heureka  Jul 21, 2017
edited by heureka  Jul 21, 2017
 #1
avatar
0

Your series can be summed up and it converges to 2 as follows:

 ∑[(1 / (2^n) * n), n, 1, 1000] =~2

Guest Jul 20, 2017
 #2
avatar+19653 
+1
Best Answer

Compute

\(1 \cdot \frac {1}{2} + 2 \cdot \frac {1}{4} + 3 \cdot \frac {1}{8} + \dots + n \cdot \frac {1}{2^n} + \dotsb.\)

 

Let \(r =\frac12\)

 

\(\begin{array}{|rcll|} \hline s_n &=& 1 \cdot \frac {1}{2} + 2 \cdot \frac {1}{4} + 3 \cdot \frac {1}{8} + \dots + n \cdot \frac {1}{2^n} \\\\ && r = \frac12 \\\\ \hline s_n &=& 1\cdot r + 2\cdot r^2 + 3\cdot r^3 + \dots + n \cdot r^n \\ rs_n &=& \qquad \quad 1\cdot r^2 + 2\cdot r^3 + \dots + (n-1) \cdot r^n + n\cdot r^{n+1} \\ \hline s_n -r\cdot s_n &=& r+r^2+r^3+ \dots +r^n-n\cdot r^{n+1} \\ s_n\cdot(1-r) &=& \underbrace{( r+r^2+r^3+ \dots +r^n )}_{=S_n} -n\cdot r^{n+1} \\ \hline && S_n = r+r^2+r^3+ \dots +r^n \\ && rS_n = \quad r^2+r^3 + \dots + r^{n+1} \\ \hline && S_n -r\cdot S_n = r - r^{n+1} \\ && S_n\cdot (1-r) = r - r^{n+1} \\ && S_n = \frac{r - r^{n+1}}{1-r} \\ \hline s_n\cdot(1-r) &=& \underbrace{( r+r^2+r^3+ \dots +r^n )}_{=S_n} -n\cdot r^{n+1} \\ s_n\cdot(1-r) &=& \frac{r - r^{n+1}}{1-r} -n\cdot r^{n+1} \\ s_n &=& \frac{1}{1-r} \cdot \Big( \frac{r - r^{n+1}}{1-r} -n\cdot r^{n+1} \Big) \\\\ && \frac{1}{1-r} = 2 \\\\ s_n &=& 2 \cdot \Big( 2\cdot(r - r^{n+1}) -n\cdot r^{n+1} \Big) \\ s_n &=& 2 \cdot ( 2\cdot r - 2\cdot r^{n+1} - n\cdot r^{n+1} ) \\ s_n &=& 2 \cdot r\cdot ( 2 - 2\cdot r^n - n\cdot r^n ) \\ \\ \mathbf{s_n} & \mathbf{=} & \mathbf{2 \cdot r\cdot \Big( 2 - (2+n)\cdot r^n \Big)} \quad & | \quad r=\frac12 \\ \\ s_n & = & 2 \cdot \frac12 \cdot \Big( 2 - (2+n)\cdot (\frac12)^n \Big) \\ s_n & = & 2 - (2+n)\cdot \frac{1}{2^n} \\ \\ \mathbf{s_n} & \mathbf{=} & \mathbf{2 - \frac{2+n}{2^n} } \\ \hline \end{array}\)

 

laugh

heureka  Jul 21, 2017
edited by heureka  Jul 21, 2017

6 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.